Bahaya Takfir dalam Islam: Analisis Kritis terhadap Dampak Teologis dan Sosial - Alif Via Rahmawati; Sylvia Zakiyyatul Miskiyyah; Mulia Eka Wati Maily (Yayasan Mutiara Hati Moeslem, 2026)
Takfir (declaring someone an unbeliever) is a highly sensitive theological issue in Islam because it has serious implications for creed, law, and social matters. Reckless practices of takfir, carried out without solid scholarly and methodological foundations, have the potential to cause conflict, disintegration within the Muslim community, and deviation from the principle of caution in Islamic law. This study aims to examine the meaning of kafir and takfir from an Islamic perspective, elaborate on the dangers of baseless takfir practices, and analyze scholars' views regarding the limits and conditions in issuing a kafir verdict on a Muslim. This research uses a library research method, through analysis of primary and secondary sources, including the Qur’an, hadith, and works of classical and contemporary scholars. The study finds that scholars agree on the need for extreme caution regarding the issue of takfir, by establishing strict conditions, such as clarity The clarity of the argument, the delivery of evidence, the absence of coercion, intent, as well as the distinction between the disbelief of an action and the doer of the action. This study emphasizes that a cautious approach in declaring someone an unbeliever (takfir) is part of the effort to maintain the welfare of the community and aligns with the principles of religious moderation (wasathiyyah Islamiyyah). Therefore, a verdict of disbelief cannot be issued lightly and must be entrusted to competent scholarly authorities.